Rubber (SEBS-g-MA) Toughened Flame-Retardant Polyamide 6: Microstructure, Combustion, Extension, and Izod Impact Behavior. Issue 8 (24th May 2018) - Wu, Hao; Krifa, Mourad; Koo, Joseph H.
ABSTRACT: In this study, elastomer toughening is explored as a means of recovering ductility of polyamide 6/intumescent flame-retardant composite systems. This was achieved using a maleic anhydride modified SEBS elastomer incorporated into the system by twin-screw melt extrusion. TEM micrographs show an even distribution of both flame retardant and elastomer particles. The effects of elastomer content on mechanical properties, Izod impact behavior, and flammability of the polymer system were investigated. The incorporation of flame retardant significantly degraded the elongation and ductility of the polymer system. The addition of the elastomer succeeded in significantly enhancing the Izod impact strength and partially recovering the elongation at break without compromising the flame-retardant performance. Micro-scale Combustion Calorimeter (MCC) tests show that samples containing both elastomer and FR additives exhibit slightly improved combustion properties compared to the original polyamide 6/intumescent flame-retardant system. Rubber loadings of up to 15 wt% were possible while still achieving the highest UL-94 V0 flame exposure rating indicating a self-extinguishing and non-drip behavior. GRAPHICAL ABSTRACT: